Про треті модулі неперервності - Безкрила, С.І.; Нестеренко, О.Н.; Чайковський, А.В. (Український математичний журнал, 2014)
An inequality for the third uniform moduli of continuity is proved. This inequality implies that an arbitrary 3-majorant is not necessarily a modulus of continuity of order 3.